Cultural Contents in an English as a Foreign Language (EFL) Textbook for Senior High School - Sari Diana (ENGLISH EDUCATION DEPARTMENT - UNIVERSITAS SINGAPERBANGSA KARAWANG, 2021)
This research investigates the cultural contents in an English textbook for senior high school which has been published by Ministry of Education. To reveal what cultures are represented in the textbook, the cultural contents in this study are categorized into the source culture, the target culture, or the international culture (Cortazzi & Jin, 1999). This study is a qualitative research which employs a cultural analysis toward an English textbook for senior high school students of grade XI. The data for the study are in the form of written texts and illustrations that may accompany the reading contents. The research finds that source culture is more dominant in the textbook, and it is presented in form of historical facts and names chosen for characters, public figures and locations in the textbook. Based on the findings it is recommended that more target culture and international culture be included in the textbook.